Experimental and numerical assessment of fracture toughness of dual-phase austempered ductile iron - Basso, Alejandro Daniel (2010)
The effects of the microstructure topology on the fracture toughness of dual-phase austempered ductile iron are studied in this paper by means of finite element modelling and experimental testing. To this end, specimens with matrix microstructures ranging from fully ferrite to fully ausferrite were studied and the preferential zones and phases for crack propagation were identified in every case. The effectiveness of the ausferrite phase as a reinforcement of the ferritic matrix via the encapsulation of the brittle and weak last-to-freeze (LTF) zones was confirmed. The toughening mechanism is consequence of the increment in the crack path longitude as it avoids the encapsulated LTF zones. Besides, the presence of small pools of allotriomorphic ferrite increase the crack propagation resistance ofthe ausferrite-ferrite matrices. © 2009 Blackwell Publishing Ltd.